Factors Influencing English Language Training Centres Choice Among Parents in Danang City - Nguyen, Thi Hong Thuy; Trung, Nguyen Xuan (Business Management and Strategy, 2022)
Foreign language learning has been in high demand among today’s young people. Current language training goes beyond traditional school classes and takes place in foreign language centers, where expat instructors collaborate with Vietnamese teachers. The acquisition of new languages, including English, has therefore been effectively promoted. The purpose of this study is to uncover the factors that affect parent decisions regarding selecting an English center within Danang City, with the goal of proposing performance improvement solutions for local enterprises operating in the field.